Indicated school-based intervention to improve depressive symptoms among at risk Chilean adolescents: a randomized controlled trial - Gaete, Jorge; Martinez, Vania; Fritsch, Rosemarie; Rojas, Graciela; Montgomery, Alan A.; Araya, Ricardo (BioMed Central, 2016)
Background: Depression is a disabling condition affecting people of all ages, but generally starting during adolescence. Schools seem to be an excellent setting where preventive interventions may be delivered. This study aimed to test the effectiveness of an indicated school-based intervention to reduce depressive symptoms among at-risk adolescents from low-income families. Methods: A two-arm, parallel, randomized controlled trial was conducted in 11 secondary schools in vulnerable socioeconomic areas in Santiago, Chile. High-risk students in year 10 (2° Medio) were invited to a baseline assessment (n = 1048). Those who scored ≥10 (boys) and ≥15 (girls) in the BDI-II were invited to the trial (n = 376). A total of 342 students consented and were randomly allocated into an intervention or a control arm in a ratio of 2:1. The intervention consisted of 8 group sessions of 45 min each, based on cognitive-behavioural models and delivered by two trained psychologists in the schools. Primary (BDI-II) and secondary outcomes (measures of anxiety, automatic thoughts and problem-solving skills) were administered before and at 3 months post intervention. The primary outcome was the recovery rate, defined as the proportion of participants who scored in the BDI-II <10 (among boys) and <15 (among girls) at 3 months after completing the intervention. Results: There were 229 participants in the intervention group and 113 in the control group. At 3-month follow-up 81.4 % in the intervention and 81.7 % in the control group provided outcome data. The recovery rate was 10 % higher in the intervention (50.3 %) than in the control (40.2 %) group; with an adjusted OR = 1.62 (95 % CI: 0.95 to 2.77) (p = 0.08). No difference between groups was found in any of the secondary outcomes. Secondary analyses revealed an interaction between group and baseline BDI-II score. Conclusions: We found no clear evidence of the effectiveness of a brief, indicated school-based intervention based on cognitive-behavioural models on reducing depressive symptoms among Chilean adolescents from low-income families. More research is needed in order to find better solutions to prevent depression among adolescents.